Respecting Elders and Community Norms: Understanding the Adat Prohibition on 'Nikah Malem Songo Geblake Mbah - Rinwanto Rinwanto; Nurul Hakim; Farida Isroani; Yudi Arianto (Indonesian Journal of Cultural and Community Development, 2023)
This study aims to explore the prohibition of "nikah malem songo geblake mbah" in the Jegulo Soko Tuban community, which is an adat (customary) prohibition outside of Islamic law. Using a normative-fiqhiyyah and sociological approach, the study found that the prohibition of "nikah malem songo geblake mbah" is based on sadd al-dhari'ah, as it is believed to potentially cause harm and disrespect to elders, and goes against community norms. The research also identified various factors contributing to the prohibition. In terms of Islamic law, the study concludes that "nikah malem songo geblake mbah" is prohibited, as it goes against the principles of kemaslahatan (public interest) and may cause harm. Therefore, it is recommended that the community continues to uphold the prohibition to maintain social harmony and respect for cultural norms.Highlights: The prohibition of 'nikah malem songo geblake mbah' is an adat rule outside of Islamic law. The prohibition is based on the principles of sadd al-dhari'ah and may cause harm and disrespect to elders. Upholding the prohibition is necessary to maintain social harmony and respect for cultural norms.